PENGARUH JARAK, KEMIRINGAN, DAN INTENSITAS CAHAYA PADA ANALISIS UKURAN PORI MASKER KAIN MENGGUNAKAN SMARTPHONE - Meri Hamdini; Diana Novita Sari; Susanti Susanti; Yuant Tiandho (Prodi Fisika FST UNJA, 2021)
One of the common strategies used to minimize the spread of Covid-19 is to wear a cloth mask. Cloth masks have a lower effectiveness value compared to other types of masks but have the potential to be used as an alternative, especially during a pandemic. Smartphone can be used as an initial idea for determining the quality of a cloth mask. In taking pore images, there are factors that have the potential to affect the results of pore size, namely distance, angle of inclination, and light intensity. Taking photos of masks with a magnification application is done with three variations, namely distance, angle, and light intensity. The distance for taking pore images is varied to 3, namely 8 cm; 10 cm; and 12 cm. The image capture angle is varied to 0p; 5o; and 10o. measurement using a distance of 10 cm has the closest value from the measurement results by taking images using a microscope, which is 0.232 mm. In the variation of the angle, the angle that is parallel or 0o to the plane of the cloth mask has a value that is close to the microscope measurement, which is 0.232 mm. The light intensity measured using a lux meter which shows the results of 240 has a value that is closest to taking an image using a microscope, which is 0.221 mm.